2022
DOI: 10.1111/age.13201
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes associated with feather color in Liancheng white duck using FST analysis

Abstract: Liancheng white duck has two phenotypic traits: white feather and black beakblack foot, but the genes controlling these phenotypic traits are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Through analysis and literature review, it was evident that the significant DEGs included genes associated with melanin synthesis, such as SLC45A2 , TYRP1 , vitamin D receptor ( VDR ), opsin 5 ( OPN5 ), and docking protein 5 ( DOK5 ). These genes play crucial roles in regulating melanin synthesis[ 13 , 14 , 15 , 16 , 17 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through analysis and literature review, it was evident that the significant DEGs included genes associated with melanin synthesis, such as SLC45A2 , TYRP1 , vitamin D receptor ( VDR ), opsin 5 ( OPN5 ), and docking protein 5 ( DOK5 ). These genes play crucial roles in regulating melanin synthesis[ 13 , 14 , 15 , 16 , 17 ]…”
Section: Resultsmentioning
confidence: 99%
“…This pathway is involved in melanoma growth, invasion, and metastasis[ 27 , 28 ]. Wang[ 17 ]has observed that DOK5 leads to abnormal melanin transfer in Liancheng white ducks, resulting in feather whitening, and that its polymorphism is also associated with feather color.…”
Section: Discussionmentioning
confidence: 99%
“…It activates the TYR core enhancer, which helps to regulate the tyrosinase gene in melanocytes ( Yun et al, 2019 ). At present, the predominant candidate genes related to duck feather color are TYR ( Sultana et al, 2018 ), TYRP1 ( Xi et al, 2020 ), DCT ( Sultana et al, 2018 ), MC1R ( Liu et al, 2023a ), EDNRB2 ( Guo et al, 2022 ), and MITF ( Zhou et al, 2018 ; Lin et al, 2019 ; Wang et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…qPCR was performed using SYBR Green Real-time PCR Master Mix (TaKaRa, China). 2 −ΔΔCt method and Student's t tests were used for comparative analysis of gene differential expression ( Wang et al, 2022a , b ). p < 0.05 and p < 0.01 were considered significant and highly significant, respectively.…”
Section: Methodsmentioning
confidence: 99%